BOOK REVIEW: Management Accounting - Jusoh, Ruzita (Asian Journal of Business and Accounting, 2017)
Book Title: Management Accounting Authors: Nor Aziah Abu Kasim, Rozita Amirudddin, Rozainun Abdul Aziz, and Che Hamidah Che Puteh. Publisher: Oxford, University Press ISBN: 978â€983â€45096â€0â€6 Number of Pages: 333